2005
DOI: 10.1128/iai.73.4.2222-2231.2005
|View full text |Cite
|
Sign up to set email alerts
|

Function of Neisserial Outer Membrane Phospholipase A in Autolysis and Assessment of Its Vaccine Potential

Abstract: Outer membrane phospholipase A (OMPLA) is an outer membrane-localized enzyme, present in many gram-negative bacterial species. It is implicated in the virulence of several pathogens. Here, we investigated the presence, function, and vaccine potential of OMPLA in the human pathogen Neisseria meningitidis. Immunoblot analysis showed the presence of OMPLA in 28 out of 33 meningococcal strains investigated. The OMPLAnegative strains all contained a pldA gene, but these alleles contained premature stop codons. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 48 publications
1
43
0
2
Order By: Relevance
“…Moreover, our experiments revealed ubiquitous expression of a number of recognized proteins including an outer membrane-localized enzyme, Phospholipase A, and a surface-exposed lipoprotein Ng-MIP (Table II). Concurring with our data, these proteins were found invariably expressed in many different GC and meningococcal isolates (78,79). Perhaps not surprisingly, proteins participating in the process of outer membrane biogenesis, BamA (Omp85) and BamD (ComL), were identified by iTRAQ experiments as equally present in GC strains (Table II).…”
Section: Strategy For Rigorous Proteomic Profiling Of the Gc Cell Envsupporting
confidence: 83%
“…Moreover, our experiments revealed ubiquitous expression of a number of recognized proteins including an outer membrane-localized enzyme, Phospholipase A, and a surface-exposed lipoprotein Ng-MIP (Table II). Concurring with our data, these proteins were found invariably expressed in many different GC and meningococcal isolates (78,79). Perhaps not surprisingly, proteins participating in the process of outer membrane biogenesis, BamA (Omp85) and BamD (ComL), were identified by iTRAQ experiments as equally present in GC strains (Table II).…”
Section: Strategy For Rigorous Proteomic Profiling Of the Gc Cell Envsupporting
confidence: 83%
“…This antigen was present in roughly equal amounts in both vaccines, but the FetA in MeNZB had a slightly lower molecular weight in polyacrylamide gels, consistent with a deletion in the main variable immunogenic region of this protein compared with the FetA in MenBvac (49,53). Although outer membrane phospholipase A is present in strain 44/76 and was identified in OMVs from NZ98/254 (8,57), no IgG reaction was observed with this protein expressed in OMVs from a PorA-negative 44/76 strain, in support of the findings of a recent study (8).…”
Section: Vol 14 2007 Immune Responses To Two Serogroup B Omv Vaccinmentioning
confidence: 90%
“…Thus, lysis occurring in our amiC mutant aggregates may be a direct effect of outer membrane instability resulting from the unusual cell architecture. It is known that autolysis can be triggered by membrane instability, and it was recently shown that N. gonorrhoeae mutants deficient in phospholipase A are decreased in autolysis (4). Alternatively, the absence of AmiC may allow another peptidoglycanase to act in an uncontrolled manner, leading to autolysis.…”
Section: Discussionmentioning
confidence: 99%